Application of Culture Introduction to Riau Province Based on Android (Case Study in SMA Negeri 1 Cerenti, Kuantan Singingi District) - Yulisman, Yulisman; Serdiansah, Serdiansah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Current technological developments have an impact on the application of technology in the field of education, especially in the learning process. SMA Negeri 1 Cirenti is a school located in Riau Province, Kuantan Singingi Regency. The learning process in SMA Negeri 1 Cirenti which has been done in a conventional way, namely the teacher explains the subject matter based on books and other supporting media such as material about the introduction of culture in Riau Province. The material is very important for students to preserve culture and customs in the future, and so that the material is more interesting, the use of technology as a learning media that can be accessed wherever students are. Smart phone technology can be utilized in the education sector by creating applications that are capable of supporting learning media. The purpose of this study is to design and create an Android-based mobile phone application as an application for learning introduction to culture in Riau Province. Making this application uses a prototype development method with eclipse software and java programming language, as well as for testing applications with the blackbox method. The results of this study are applications that introduce educative and interactive culture of Riau Province based on Android to students and teachers with applications that can be directly installed on a smart phone.